Factors Affecting Decision Support System: Knowledge, Training, Ease of Use - Ade Saputra, Guntur; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2023)
In the rapidly changing landscape of modern organizations, the ability to make informed and timely decisions is crucial. Decision Support Systems (DSS) have emerged as vital tools to aid decision-makers by providing valuable insights and assistance in the decision-making process. This journal explores the critical factors influencing the adoption and effectiveness of DSS, with a specific focus on the variables of knowledge, training, and ease of use. The research employed the research library method, conducting a comprehensive review of existing literature to advance understanding of the factors influencing DSS. The results and discussions highlight the significance of knowledge, training, and ease of use in the successful utilization of DSS. Users' computer proficiency, familiarity with similar systems, training, and system intuitiveness all contribute to the effectiveness and acceptance of DSS. Tailoring DSS to individual needs and knowledge levels can enhance their ability to support decision-making in various contexts.